ANALYSIS OF TIME AND COST CONTROL IN AN ASRAMA HAJI PONTIANAK BUILDING CONSTRUCTION PROJECT USING THE EARNED VALUE ANALYSIS METHOD - Putri, Imas Yuniar; Lusiana, Lusiana; Rafie, Rafie; Syahrudin, Syahrudin; Nuh, Safaruddin M. (Jurnal Teknik Sipil, 2024)
Efficient management of construction projects requires meticulous oversight of both time and cost elements. This investigation focuses on employing Earned Value Analysis (EVA) to supervise and regulate the Asrama Haji Pontianak Building Construction Project. EVA furnishes indispensable insights conducive to proactive decision-making by evaluating the project's advancement vis-Ã -vis predetermined schedules and financial plans. The study critically assesses the utilization of EVA, scrutinizing its efficacy in forecasting project outcomes, detecting deviations, and facilitating prompt corrective measures. A thorough examination of time and cost performance indicators, including the Schedule Performance Index (SPI) and Cost Performance Index (CPI), illuminates the project's adherence to established schedules and budgets. Furthermore, it delves into the challenges encountered and the strategies employed in integrating EVA into project management methodologies. From the results of the analysis of the time and cost of the Asrama Haji Pontianak building construction project experiencing a delay of 1 week from the planned time and the estimated total final project cost of Rp. 21.400.271.242,98 is less than the planned cost of Rp. 21.876.433.145,64.The findings enhance the understanding of EVA's role in optimizing time and cost control, offering valuable insights for future construction projects aiming for improved performance and efficiency.